Interaction between Deformation and Crack Initiation under Vickers Indentation in Na2O–TiO2–SiO2 Glasses - Scannell, Garth; Laille, Denis; Célarié, Fabrice; Huang, Liping; Rouxel, Tanguy (Frontiers in Materials, 2017)
An observed minimum in the critical crack initiation load at Poisson's ratio (ν) of 0.21-0.22 in Na2O-TiO2-SiO2 glasses was investigated. Vickers indentation was used to examine hardness and average cracking length, fracture toughness was measured through the single-edge pre-cracked beam method (SEPB), and volumes of densification and shear flow around indents were measured using atomic force microscopy (AFM). Relations between the critical crack initiation load and hardness, average crack length, fracture toughness, and the volume fractions of densification and shear flow were studied. No correlations were observed between hardness, average crack length, or fracture toughness with the critical crack initiation load. A link between the minimum in crack initiation load and a change in deformation mechanisms (densification vs. shear flow) was observed.